(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
A method for contactless temperature measurement with photodetectors in different operating modes has been developed. It is based on the periodic change of the spectral sensitivity of the photodiode depending on the applied reverse voltage. This is accomplished by switching the photodiode within one measurement from photovoltaic to photoconductive mode. For this purpose, the scheme of the respective electronic key has been developed.